Epimuscular myofascial force transmission from biarticular rectus femoris elongation increases shear modulus of monoarticular quadriceps muscles. (9th June 2021) - Yanase, Ko; Yagi, Masahide; Nakao, Sayaka; Motomura, Yoshiki; Umehara, Jun; Hirono, Tetsuya; Komamura, Tomohito; Miyakoshi, Kosuke; Ibuki, Satoko; Ichihashi, Noriaki
Abstract: This study aimed to examine the effect of rectus femoris (RF) elongation with passive hip angle change on the shear moduli of the vastus lateralis (VL) and medialis (VM) to verify whether Epimuscular myofascial force transmission (EMFT) occurs in the human quadriceps. Fourteen healthy men participated in this study. The shear moduli of the RF, VL, and VM were measured in four hip positions: flexion (Flex), extension and abduction (Ext-Abd), extension (Ext), and extension and adduction (Ext-Add). As the behavior of shear moduli may differ depending on the parts of the vasti muscles, we measured the medial and lateral parts of the VL (Medial-VL and Lateral-VL) and VM (Medial-VM and Lateral-VM). The shear moduli at the Ext and Ext-Add positions were higher than at the Flex position in the RF, VL, and VM. The shear moduli during Ext and Ext-Add were higher than at the Ext-Abd in the RF, VL, and Lateral-VM. Moreover, the shear modulus of the Lateral-VM was higher than of the Medial-VM (Flex: 8.5% higher; Ext-Abd: 15.6%; Ext: 30.2%; Ext-Add: 32.6%). The shear moduli of the VL and VM, which are monoarticular muscles of the knee, increased with passive hip extension or adduction with extension, even when the knee angle was kept constant. The results suggest that EMFT occurs in the quadriceps, and EMFT had a great impact in the Lateral-VM, which is anatomically adjacent to the RF, but it had little effect in the Medial-VM, which is further away from the RF.